Analisis Pendapatan Usahatani Padi Organik dan Kontribusinya Terhadap Pendapatan Rumahtangga Di Kecamatan BTS Ulu Kabupaten Musi Rawas - Ira Primalasari Ira; May Shiska Puspitasari (Politeknik Negeri Lampung, 2021)
This study aims to analyze amount of income and calculate the contribution of organic rice farming to household income in Suka Makmur Village, BTS Ulu District. The research was conducted in Suka Makmur Village, BTS Ulu District. The research was conducted in September-October 2020. This location was chosen because it has a large number of organic rice farmers and has been used as a source of household income in Suka Makmur Village. Respondents in this study were taken based on purposive sampling method where all members of the population were used as respondent data in the study. This is primary data. Primary data in this study were obtained through interviews with questionnaires for organic rice farmers. Interviews were conducted with the aim of obtaining information directly from the respondents, which were related to the research topic. The number of samples of organic rice farmers were 77 respondents who were administrators and members of the organic rice group. This research used descriptive quantitative data analysis. The results showed that the average income of organic rice farmers in Suka Makmur Village, BTS Ulu District was 34,100,000 / year. The largest contribution of organic rice farming income to family income was 34.12%. This shows that the results of organic rice farming are the main source of income to meet their daily needs.